Ilmu Dalam Perspektif Al-Ghazali dan Ibnu Rusyd - Dedi Mustofa (Kopertais Wilayah XV Lampung, 2021)
Science can be useful for human life but can also be detrimental to human life. This is because the subjects of the users of knowledge are different so that they have different morals. In the study of science, there is one figure who is well-known in the field of Sufism and is competent in the field of philosophy. Imam al-Ghazali is one of the famous scholars and thinkers to date and some of his work as a guide for Muslims. There are several procedures for acquiring true knowledge according to Imam al-Ghazali, where such procedures must be adopted gradually in a systematic step coverage. This systematic step was stated by Imam al-Ghazali in a state that consists of 6 stages, namely intention/determination, repentance, mujahadah, muzakarah, mukasyafah and musyahadah. Ibn Rushd did three attempts at a time that is defending the philosophers who dikafirkan al-Ghazali, clarifying understanding of philosophy and refute understand Al-Ghazali. The defense of philosophers is carried out by formulating the harmonization of religion and philosophy.